Knowledge management audit of the Japan International Cooperation Agency Philippines Office - San Juan, Kristine May B. (University of the Philippines Diliman, 2007)
The project aims to identify and address the gaps and weaknesses of three areas : 1) the knowledge acquisition methods, 2) the knowledge sharing methods, and 3) the knowledge repository or banking methods in JICA Philippines. To achieve the objectives mentioned, the project entails assessing the knowledge management needs of JICA Philippines. The proponent of the project will identify the knowledge needs of each section which are necessary in the undertaking of JICA's general tasks, and will identify the knowledge needs of each section which are necessary in the undertaking of JICA's general tasks, and will identify the means by which these knowledge needs are acquired by each section. The knowledge needs that are left out or not effectively acquired through the existing knowledge acquisition methods will be identified as "knowledge gaps" in the acquisition methods. In this project, the gaps in the knowledge sharing methods will be identified by tracking whether there are knowledge that are available in sections within in JICA which are not shared internally with other sections in JICA and externally to other persons and entities who may find the knowledge useful in their operations. The proponent will identify the knowledge banking gaps by tracking how the knowledge flows within and outside the organization to find out where knowledge is spilled or are not effectively elicited, shared and reposited. The researcher will conduct the assessment through 1) the summarization of the knowledge needs and sources of each section from formal surveys using questionnaires with at least one respondent per section; 2) verification of data collected through interviews and one-on-one consultations or informal surveys through email and casual discussions with the survey respondents and 3) identification of knowledge needs that are not met and knowledge sources that are not utilized. To address the knowledge management gaps that will be identified, the proponent will look into and recommend best practices and state of the art knowledge management tools applied and found effective in other donor organizations in light of the concepts learned from the Technology Management Course, especially from the subject TM 298 : Knowledge Management. Essentially, the Project will enable the proponent to assess the areas where knowledge management initiatives are needed and to determine what KM tools and solutions would be appropriate in order to enable better knowledge acquisition, sharing and banking in the organization. This project is being undertaken in partial fulfillment of the requirements of the Masters in Technology Management Program.